2000
DOI: 10.1128/aac.44.11.3049-3054.2000
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone Resistance in Clinical Isolates of Streptococcus pneumoniae : Contributions of Type II Topoisomerase Mutations and Efflux to Levels of Resistance

Abstract: We report on amino acid substitutions in the quinolone resistance-determining region of type II topisomerases and the prevalence of reserpine-inhibited efflux for 70 clinical isolates of S. pneumoniae for which the ciprofloxacin MIC is >4 g/ml and 28 isolates for which the ciprofloxacin MIC is <2 g/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 29 publications
4
97
1
Order By: Relevance
“…Ciprofloxacin and levofloxacin preferentially target ParC, whereas moxifloxacin and gatifloxacin target both ParC and GyrA (15). Prior to the introduction of gatifloxacin and moxifloxacin, all isolates with mutations observed in the QRDRs of S. pneumoniae had mutations in the parC gene (3,10). Since the introduction of gatifloxacin and moxifloxacin, the number of isolates with parC mutations has remained stable, but there has been an increase in the proportion of isolates with gyrA-only mutations (12,13,24).…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin and levofloxacin preferentially target ParC, whereas moxifloxacin and gatifloxacin target both ParC and GyrA (15). Prior to the introduction of gatifloxacin and moxifloxacin, all isolates with mutations observed in the QRDRs of S. pneumoniae had mutations in the parC gene (3,10). Since the introduction of gatifloxacin and moxifloxacin, the number of isolates with parC mutations has remained stable, but there has been an increase in the proportion of isolates with gyrA-only mutations (12,13,24).…”
Section: Discussionmentioning
confidence: 99%
“…Not all amino acid substitutions cause the same level of resistance: mutations in parC alone, such as Ser79-Phe, Ser79Tyr, Ser79Ala, Asp83Gly and Asp83Tyr, confer a low level of resistance to FQ. When combined with mutations in gyrA such as Glu85Lys, Ser84Tyr and Ser84Phe, some mutations confer high-level resistance [45,46]. In addition, it was confirmed that parC is the primary target for FQ, and mutations in this subunit were shown to be the crucial first step for the acquisition of a high level of resistance [45,47].…”
Section: Fluoroquinolone (Fq) Resistancementioning
confidence: 97%
“…Mutations in parE and gyrB have also been reported, but to a lesser extent (2,23,30). Reduced susceptibility to fluoroquinolone may also be due to altered accumulation of the drug or efflux, but this plays a less significant role (31).…”
mentioning
confidence: 99%